Multifaceted mechanisms of HIV-1 entry inhibition by human α-defensin. - Demirkhanyan, L; Marin, M; Padilla-Parra, S; Zhan, C; Miyauchi, K; Jean-Baptiste, M; Novitskiy, G; Lu, W; Melikyan, G (2012)
The human neutrophil peptide 1 (HNP-1) is known to block the human immunodeficiency virus type 1 (HIV-1) infection, but the mechanism of inhibition is poorly understood. We examined the effect of HNP-1 on HIV-1 entry and fusion and found that, surprisingly, this α-defensin inhibited multiple steps of virus entry, including: (i) Env binding to CD4 and coreceptors; (ii) refolding of Env into the final 6-helix bundle structure; and (iii) productive HIV-1 uptake but not internalization of endocytic markers. Despite its lectin-like properties, HNP-1 could bind to Env, CD4, and other host proteins in a glycan- and serum-independent manner, whereas the fusion inhibitory activity was greatly attenuated in the presence of human or bovine serum. This demonstrates that binding of α-defensin to molecules involved in HIV-1 fusion is necessary but not sufficient for blocking the virus entry. We therefore propose that oligomeric forms of defensin, which may be disrupted by serum, contribute to the anti-HIV-1 activity perhaps through cross-linking virus and/or host glycoproteins. This notion is supported by the ability of HNP-1 to reduce the mobile fraction of CD4 and coreceptors in the plasma membrane and to precipitate a core subdomain of Env in solution. The ability of HNP-1 to block HIV-1 uptake without interfering with constitutive endocytosis suggests a novel mechanism for broad activity against this and other viruses that enter cells through endocytic pathways.